Kårebolssätern and other shielings - the emergence and development of Swedish transhumant pastoralism - Eva Svensson; Susanne Pettersson; Annie Johansson (Pastoralism)
Transhumant pastoralism, characterized by the seasonal movement of livestock, has been a traditional practice in various forms globally for millennia. The Scandinavian shieling system—specifically, the Kårebolssätern site—exemplifies this practice, where designated areas provide grazing and dairy processing facilities. However, many of these systems, including Kårebolssätern, have faced abandonment or decline, primarily due to modernization and industrial forces. An interdisciplinary research project compared Kårebolssätern’s history to other shielings in Sweden. The study utilized various methodologies, including pollen analysis, archaeological mapping, and historical documentation, to trace human impact and land use, indicating shifts between grazing and cereal cultivation. Findings demonstrated that Kårebolssätern had significant early cultivation of barley and hemp, and by the 13th century, its use intensified amidst changes in local agricultural conditions. Four chronological phases regarding the emergence and development of Swedish shielings over two millennia were detected. The results offer insights into the adaptability of shielings amidst socio-economic transformations. As modern pressures threaten the remaining shielings, preserving their historical significance and adaptive strategies may provide pathways for their future survival. The study ultimately highlights the resilience of pastoral practices within evolving landscapes.